Relação entre as motivações no voluntariado em eventos esportivos e felicidade no trabalho: um olhar sobre a retenção de voluntários em eventos na área esportiva no Brasil - Pereira, Hélio Araújo (2022)
Volunteer activity encompasses various segments of society, including the sector that has increasingly brought together a representative volume of people: the sporting events sector, which is the focus of this thesis. Its objective is to analyze the impact of happiness at work on the retention process in volunteering based upon the influence of the motivations of volunteers who work in sporting events in Brazil. Methodologically, we opted for quantitative research carried out through the application of scales related to volunteer motivation in sporting events, happiness at work and retention of volunteers in sporting events. This allowed us to parameterize in a way more systematic and secure the results presented here. As for the main results: the development of a scale on volunteer motivation in sporting events in Brazil; and, the finding that happiness at work influences the retention process of volunteers who work in sporting events in Brazil. Given the development of this scale, consisting of six factors and thirty-two items, it was observed that motivations positively influence the happiness at work of volunteers who work in sporting events. Such results show that motivations in volunteering at sporting events are predictors of happiness at work and that this happiness contributes to the permanence of volunteers at sporting events in Brazil.